El desafío de la marginalidad - Ribeiro, Darcy (Estudios Internacionales, 1971)
The most serious characteristic of social, economic and political disparities, which have their extreme pole in the marginalized masses, is that with the modernization of Latin American societies they only tend to increase. Indeed, far from being absorbed by the various branches of economic activity, marginal groups are on the rise. From the moment it became clear that the system is not capable of absorbing these marginal masses, they are seen as "surpluses" and their existence was identified as the most serious Latin American social problem. The historical challenge that Latin American nations face today consists, as can be seen, in finding ways to integrate these marginalized groups into more homogeneous societies.